New Records and Ecological Observations of the Previously Unreported Small Long-fingered Bat (Miniopterus pusillus) in Kerala, India - Joy, Tijo K.; Jeyapraba, L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This research contributes to the conservation efforts by shedding light on the presence of Miniopterus pusillus in Kerala, highlighting the need for continued habitat protection and species-specific studies. This study expands the bat species checklist of Kerala by documenting the previously unreported presence of Miniopterus pusillus. The study, conducted from 2016 to 2019 in the Idukki and Ernakulam districts of Kerala, India, covered three forest divisions: Malayattoor, Munnar, and Mankulam, characterized by diverse ecosystems, including tropical evergreen and semi-evergreen forests, moist deciduous forests, grasslands, and montane shola ecosystems. Morphologically, M. pusillus exhibits several distinct features that differentiate it from other insectivorous bats. These include a gracile skull, a slender jaw, a reduced coronoid process, a less developed sagittal crest, and a lower number of teeth. Miniopterus pusillus, commonly known as the Small long-fingered bat, is a rare species within the family Miniopteridae. This article emphasizes the potential for further research in the less-explored regions of the Western Ghats, underscoring the need for comprehensive biodiversity assessments in these areas.